2004
DOI: 10.1016/j.molcel.2004.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Exchange of Regions between Bacterial Poly(A) Polymerase and the CCA-Adding Enzyme Generates Altered Specificities

Abstract: Bacterial poly(A) polymerases (PAP) and tRNA nucleotidyltransferases are highly similar in sequence but display different activities: whereas tRNA nucleotidyltransferase catalyzes the addition of CCA to 3' ends of tRNAs, PAP adds poly(A) tails to a variety of transcripts. Using domain substitution experiments, we show that these enzymes follow a modular concept: exchange of N- and C-terminal regions leads to chimeric enzymes with unexpected activities, indicating that tRNA nucleotidyltransferase carries an "an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 28 publications
4
71
0
1
Order By: Relevance
“…10B). Thus, as previously observed (24), poly(A) polymerase is surprisingly nonspecific: The enzyme can add an A residue to immature tRNA-NCC in vivo (19), augmenting tRNA repair by the CCA-adding enzyme, but it can also add a poly(A) tail to mature tRNA in vitro (25) (SI Fig. 10B).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…10B). Thus, as previously observed (24), poly(A) polymerase is surprisingly nonspecific: The enzyme can add an A residue to immature tRNA-NCC in vivo (19), augmenting tRNA repair by the CCA-adding enzyme, but it can also add a poly(A) tail to mature tRNA in vitro (25) (SI Fig. 10B).…”
Section: Resultssupporting
confidence: 78%
“…The ability of this region to confer CCA-adding activity on the N terminus of poly(A) polymerase is most surprising and is consistent with the notion that scrunching, counting, and the nucleotide specificity switch in class II CCA-adding enzymes may be localized, intrinsic characteristics of the NTR active site; however, we hesitate to interpret the results of Betat et al (25) structurally because no structure has been determined for E. coli poly(A) polymerase; the helix M regions of the E. coli poly(A) polymerase and CCA-adding enzymes exhibit little if any homology; and helix M appears to be remote from the tRNA acceptor stem in the cocrystal structure of the A. aeolicus A-adding enzyme (21). (21), but homologous residues are labeled according to the BstCCA sequence (14), including M197, which is N197 in A. aeolicus.…”
Section: Resultssupporting
confidence: 78%
“…Furthermore, phylogenetic analysis indicates that collaborative CCA addition catalyzed by CC-and A-adding enzymes seems to be more widespread in bacteria than previously expected. In addition, the data not only support the idea of an ancestral CCA-adding enzyme but also indicate that nucleotidyltransferases are composed of individual modules that can be replaced by corresponding elements of related enzymes (5). Such combinations lead to proteins with new and often unexpected activities, ranging from partial to complete CCA addition.…”
Section: Discussion the Absence Of The Flexible Loop Region Is A Commsupporting
confidence: 57%
“…To address this question, the corresponding region of the CCA-adding enzyme of Bacillus subtilis (14) was introduced into the CCadding enzyme of B. halodurans. These two enzymes were chosen because they show a high sequence similarity (10), which increases the probability of catalytically active chimeric constructs, as it was successfully shown for other nucleotidyltransferase chimeras (5). For insertion, two highly conserved amino acid residues present in CC-as well as CCA-adding enzymes (E79, representing the postulated third catalytic carboxylate, and E89 in the B. halodurans enzyme) flanking the loop region were chosen as fusion positions.…”
Section: Cc-adding Enzymes Share the Deletion Of A Short Flexible Loopmentioning
confidence: 99%
“…It was also demonstrated that in CCAtrs the tRNA precursor substrate does not translocate during CCA synthesis: If the tRNA was cross-linked to the enzyme CCA was still faithfully added to the tRNA's 3′ end [61]. In addition, experiments with the E. coli CCAtr and PAP have shown that when the N-terminal catalytic and C-terminal RNA binding domains were exchanged between the two proteins, the PAP C-terminus allowed translocation of an RNA primer, thus resulting in a poly(CCA) tail added to tRNA when combined with the catalytic domain of CCAtr [62]. Conversely, when the C-terminal RNA binding domain of CCAtr was fused to the catalytic domain of bacterial PAP, the chimera acquired a CCA adding activity and added a single CCA.…”
Section: Primer Substrate Recognition and Processivitymentioning
confidence: 99%